How to minimize adverse effects of physical workplace violence on health sector workers: A preliminary study - Lu, Jingjing; Cai, Jingjing; Shao, Wenchen; Wang, Zhaocheng (Frontiers in Psychology, 2022)
Purpose: This paper is an exploratory study to investigate possible remedial measures accounting for a relatively favorable prognosis of health sector workers who have experienced physical WPV in Zhejiang province, China. Methods: Following a proportionate stratified sampling strategy, five tertiary hospitals (in the developed capital city of Hangzhou and other prefecture-level cities), eight secondary hospitals (in counties), and thirty-two primary care facilities (16 urban community health centers and 16 rural township health centers) were conveniently selected. Among 4862 valid respondents out of 6089 self-conducted questionnaires, 224 health sector workers who have been directly exposed to physical WPV in the past year were included in the present study. Results: The present study has three major findings: 1) Victims’ satisfaction with the resolution of the physical WPV conflict was directly associated with the favorable prognosis. 2) Taking days off from work after the violence can promote victims’ satisfaction with the resolution of the physical WPV conflict. 3) Knowing that relevant departments investigated the case can promote victims’ satisfaction with the resolution of the physical WPV conflict. Conclusion: We propose a combined gesture of “offering adequate days off work after physical WPV” and “every physical violence must be investigated” that should be taken by all medical institutions in China. Health sector workers who get involved in physical WPV incidents should prioritize their safety and avoid any behavior that may intensify the conflicts.